Investigating ethylene oxide exposure and its associations with kidney indicators and lipid profiles: the mediating effect of HDL in NHANES 2013-2020 - Luo, Yiheng; Xu, Duo; Zhang, Weiyong; Wang, Kai; Kuang, Mingqin; Liu, Yueyang (Frontiers in Physiology, 2025)
IntroductionEthylene oxide (EO) exposure has been associated with various health conditions, such as cancer and cardiovascular diseases. However, its potential relationships with kidney function and lipid profiles require further investigation.MethodsThis study analyzed data from 3,500 US adults participating in NHANES 2013–2020. EO exposure was assessed using hemoglobin adducts of EO (HbEO) as a biomarker. Associations with kidney and lipid parameters were evaluated using multivariate linear regression models. Mediation analysis was performed to explore the role of high-density lipoprotein (HDL) in these associations.ResultsHigher HbEO levels were significantly associated with decreased albumin (Alb) (β = −0.79, 95% CI: −1.15, −0.43) and increased blood urea nitrogen in the second and third quartiles (Q2: (β = 0.79, 95% CI: 0.34, 1.24; Q3: (β = 0.81, 95% CI: 0.35, 1.27). Uric acid (UA) showed an inverse association with the highest quartile of HbEO (β = −0.23, 95% CI: −0.36, −0.09). Log10-transformed HbEO levels were negatively associated with Alb, UA, and the UA/serum creatinine ratio. Regarding lipids, no significant associations were found with triglycerides, total cholesterol, or LDL. However, EO exposure was negatively associated with HDL levels (β = −3.57, 95% CI: −5.18, −1.96). Mediation analysis revealed that HDL mediated 6.51% of the association between EO and Alb, 12.44% with UA (inverse), and 11.01% with urinary creatinine.DiscussionEO exposure is significantly associated with alterations in kidney function and HDL levels. HDL's mediating role suggests a potential mechanism linking EO to renal biomarkers, warranting further mechanistic investigation.